Effects of prenatal exercise on fetal heart rate, umbilical and uterine blood flow: a systematic review and meta-analysis. Issue 2 (18th October 2018) - Skow, Rachel J; Davenport, Margie H; Mottola, Michelle F; Davies, Gregory A; Poitras, Veronica J; Gray, Casey E; Jaramillo Garcia, Alejandra; Barrowman, Nick; Meah, Victoria L; Slater, Linda G; Adamo, Kristi B; Barakat, Ruben; et al.
Abstract : Objective: To perform a systematic review and meta-analysis examining the influence of acute and chronic prenatal exercise on fetal heart rate (FHR) and umbilical and uterine blood flow metrics. Design: Systematic review with random-effects meta-analysis and meta-regression. Data sources: Online databases were searched up to 6 January 2017. Study eligibility criteria: Studies of all designs were included (except case studies) if published in English, Spanish or French, and contained information on the population (pregnant women without contraindication to exercise), intervention (subjective or objective measures of frequency, intensity, duration, volume or type of exercise, alone ["exercise-only"] or in combination with other intervention components [eg, dietary; "exercise + co-intervention"]), comparator (no exercise or different frequency, intensity, duration, volume and type of exercise) and outcomes (FHR, beats per minute (bpm); uterine and umbilical blood flow metrics (systolic:diastolic (S/D) ratio; Pulsatility Index (PI); Resistance Index (RI); blood flow, mL/min; and blood velocity, cm/s)). Results: 'Very low' to 'moderate' quality evidence from 91 unique studies (n=4641 women) were included. Overall, FHR increased during (mean difference (MD)=6.35bpm; 95% CI 2.30 to 10.41, I 2 =95%, p=0.002) and following acute exercise (MD=4.05; 95% CI 2.98 to 5.12, I 2 =83%, p<0.00001). The incidence of fetal bradycardia was low at rest and unchanged with acute exercise. There were no significant changes in umbilical or uterine S/D, PI, RI, blood flow or blood velocity during or following acute exercise sessions. Chronic exercise decreased resting FHR and the umbilical artery S/D, PI and RI at rest. Conclusion: Acute and chronic prenatal exercise do not adversely impact FHR or uteroplacental blood flow metrics.